Applicability of the Dietary Record by Cooked Dishes method for estimating dietary intake of populations in the areas other than where the database was developed - TAKACHI, Ribeka; HOSOI, Satoko; KITO, Kumiko; KIMIRA, Mitsuru; IWASAKI, Motoki; ISHIHARA, Junko; ISHII, Yuri (Nihon Koshu Eisei Zasshi(JAPANESE JOURNAL OF PUBLIC HEALTH), 2012)
Objectives The Dietary Record by Cooked Dishes (DRcd) method, which enables simple assessment of food and nutrient intake, is unique because it uses a nutrient database of cooked dishes. Although this method has been validated among the rural Japanese populations for which the database was developed, the applicability of the DRcd for other populations is unclear. In this study, we have examined the applicability of DRcd among an urban population. Methods Subjects were selected from among patients who underwent cancer screening between 2004 and 2006 at the Research Center for Cancer Prevention and Screening, National Cancer Center, Japan. Subjects aged 40–69 years, who lived in Tokyo and the surrounding suburbs, were stratified into groups by sex and age. A total of 144 men and women agreed to participate in the study after random selection. Subjects were instructed to keep 4-day dietary records (4d-DR) of all consumed foods and beverages, including dish names, and all dishes were then coded using DRcd codes on the basis their names. The intake of 17 food groups and 40 nutrients was estimated using the dish-based nutrient composition table of the DRcd. Simultaneously, 4d-DR were used to calculate dietary intake independently, which served as a reference. We examined the applicability of the DRcd method using percentage difference and Pearson's correlation coefficients for intakes estimated using 4d-DR and the DRcd. Moreover, the results were compared to those of a previous study. Results A total of 88% of the recorded dishes matched the dish codes of the DRcd database by name. Pearson's correlation coefficient scores of 0.6 or higher were observed for 12 and 10 food groups, and for 34 and 27 nutrients in men and women, respectively. Notably, the intake of majority of the nutrients tended to be underestimated, a difference that was more pronounced in men. In comparison with a previous study, the percentage differences and Pearson's correlation coefficient scores for intake tended to be lower in our study. Conclusion As the correlation coefficients (0.6) were high for a majority of food groups and nutrients estimated by DRcd, the DRcd method may be applicable for urban populations. However, regional intake data may be necessary for the estimation of absolute value for the intake of some nutrients.